Rahmatullah Kairanawi (1818-1891) and Munshi Mohammad Meherullah's (1861-1907) methodology in the study of Christianity : a comparative analysis - Masud, Abdullah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This thesis examines the contributions of Muslim scholars, Rahmatullah Kairanawi and Munshi Mohammad Meherullah to the study of Christianity and their methodologies, where they formulated different methods and approaches in response to Islam using similarities and differences in their discourses. This study analyses their discussions, exposures, presentations and arguments on Christian beliefs with a special focus on Rahmatullah’s masterpiece: Izhar al-Haqq (Truth Revealed) and Meherullah’s work, Kshristio Dharmer Asarats (Hollowness of Christianity) and Radde Kshristan O Dalilul Islam (Refutation of Christianity and Evidence of Islam), which greatly influenced Muslims in India. In addition, aspects of their lives, socio-political milieu, religious thoughts and scholarships on Christianity are also studied. This study applies the qualitative method for data collection and data analysis. The method is based on library research and textual analysis. A comparative study is also employed, relying on the works of both scholars. Using rational, polemical, comparative and dialogical arguments, the present treatise finds that both scholars explored the falsification, abrogation and fabrication of the Bible and Christianity accordingly. Finally, this study concludes that though some of their views on studying and counter-arguing Christianity are not so familiar in contemporary academia, RaÍmatullah Kairanawi’s and Munshi Mohammad Meherullah’s approaches and methods still offer mutually exclusive, yet dynamic, and engaging comparative theological mechanisms. This study, therefore, submits that appreciation of their approaches would help respond to the challenges in the field of comparative religious activities, both in principle and in the circumstances over space and time.